Three-Dimensional CST Parameterization Method Applied in Aircraft Aeroelastic Analysis - Hua Su; Chunlin Gong; Liangxian Gu (International Journal of Aerospace Engineering)
Class/shape transformation (CST) method has advantages of adjustable design variables and powerful parametric geometric shape design ability and has been widely used in aerodynamic design and optimization processes. Three-dimensional CST is an extension for complex aircraft and can generate diverse three-dimensional aircraft and the corresponding mesh automatically and quickly. This paper proposes a parametric structural modeling method based on gridding feature extraction from the aerodynamic mesh generated by the three-dimensional CST method. This novel method can create parametric structural model for fuselage and wing and keep the coordination between the aerodynamic mesh and the structural mesh. Based on the generated aerodynamic model and structural model, an automatic process for aeroelastic modeling and solving is presented with the panel method for aerodynamic solver and NASTRAN for structural solver. A reusable launch vehicle (RLV) is used to illustrate the process for aeroelastic modeling and solving. The result shows that this method can generate aeroelastic model for diverse complex three-dimensional aircraft automatically and reduce the difficulty of aeroelastic analysis dramatically. It provides an effective approach to make use of the aeroelastic analysis at the conceptual design phase for modern aircraft.